013: WORKFORCE GOVERNANCE: REFLECTIONS ON THE ROLE OF POSTINGS AND TRANSFERS AT THE PRIMARY HEALTH CARE LEVEL. (24th August 2015) - Garimella, Surekha; Sheikh, Kabir
Abstract : Background: Workforce governance plays a pivotal role in determining the performance and level of functioning of the health service and posting and transfer (PT) a crucial aspect of this. PT policies are important elements of health workforce planning strategy towards achieving appropriate deployment and optimal utilization of existing human health resources, as well as in planning for the future. Yet the health services in many LMICs face the challenge of ensuring appropriate workforce deployment. Objectives: How do different groups cadres of health systems experience PT? Methods: A case study was conducted at a primary health care level in the state of Tamil Nadu, India. 13 in-depth interviews with administrators and health workers were conducted along with the analysis of existing counselling policy documents. Result: The results of the study suggest that informal negotiations, deputations and diversions are used as coping mechanisms to address shortage of staff and make centers functional. Though counselling is an acceptable mediating mechanism between the authorities and health worker, some of the respondents expressed presence of inconsistency in the process. The PT policy does not allow for mutual transfers but subversions do happen through the use of informal networking that leads to manipulation of policies and guidelines towards the attainment of personal benefits. Also very little is known and talked about the impact of PT practices on health system functioning. However, responses highlight that service quality, access, continuity breaks and morale linked to PT are adversely affectedly. Conclusion: PT emerges as a complex phenomenon, shaped partially by the laws of the state and partially as a parallel system of norms and incentives requiring consideration and coordination of the interests of different groups. PT is not merely a system dysfunction, but also a potential instrument of governance innovations, procedural justice and the accountability of health services to communities.